2019
DOI: 10.1007/s11356-019-07274-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between manta trawl and in situ pump filtration methods, and guidance for visual identification of microplastics in surface waters

Abstract: Owing to the development and adoption of a variety of methods for sampling and identifying microplastics, there is now data showing the presence of microplastics in surface waters from all over the world. The difference between the methods, however, hampers comparisons, and to date, most studies are qualitative rather than quantitative. In order to allow for a quantitative comparison of microplastics abundance, it is crucial to understand the differences between sampling methods. Therefore, a manta trawl and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 35 publications
1
91
0
2
Order By: Relevance
“…The classifications are also often selected based on the analyst's perception rather than objective particle descriptors. Therefore, a visualphysical-chemical classification scheme with guidelines "MyVISPEC" was recently presented (Karlsson et al 2020).…”
Section: Pre-selection By Manual Sortingmentioning
confidence: 99%
“…The classifications are also often selected based on the analyst's perception rather than objective particle descriptors. Therefore, a visualphysical-chemical classification scheme with guidelines "MyVISPEC" was recently presented (Karlsson et al 2020).…”
Section: Pre-selection By Manual Sortingmentioning
confidence: 99%
“… 17 At the other end of the scale, sampling volume determines the detection limit for large particles, where larger particles with a low frequency of occurrence are simply missed when the volume is too small. 15 , 18 Therefore, the aforementioned differences in methods have resulted in data incomparability. Third, conversion from number to mass concentrations (or vice versa) is usually done assuming microplastic particles to have a certain fixed shape (e.g., spherical) with the density of a discrete polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hydrodynamic conditions, observations can be affected by the microplastic sampling method, e.g., net tows, grab samples, or filtering pumps (Hidalgo-Ruz et al, 2012;Prata et al, 2019). Some work has been done to address variability in measurements across methods (e.g., Setälä et al, 2016;Barrows et al, 2017;Karlsson et al, 2019); these studies have demonstrated that net tows can both under-sample and over-sample relative to other measurement techniques. While net tows are ideally conducted under calm conditions (e.g., sea states with Beaufort scales of 0-2) (Viršek et al, 2016), microplastics observations have been reported from conditions with Beaufort scales up to 5 (Eriksen et al, 2014;Kooi et al, 2016;Poulain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%